2009
DOI: 10.1175/2008jas2851.1
|View full text |Cite
|
Sign up to set email alerts
|

Linear Theory Calculations for the Sea Breeze in a Background Wind: The Equatorial Case

Abstract: The equatorial coastal circulation is modeled in terms of the linear wave response to a diurnally oscillating heat source gradient in a background wind. A diurnal scaling shows that the solution depends on two parameters: a nondimensional coastal width ℒ and a nondimensional wind speed 𝒰. The solutions are interpreted by comparing to the 𝒰 = 0 theory of Rotunno. For 𝒰 ≠ 0 the Fourier integral solution consists of three distinct wave branches. Two of these branches correspond to the prior no-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…Many theoretical studies, for example, Nielsen‐Gammon (), Qian et al . () and Rotunno (), have also indicated that in low latitudes (30°N) the sea breeze circulation can occur out of phase with the diurnal heating cycle and the flow becomes antitriptic (i.e., based on local pressure gradient and friction forces). This is especially true for the SRS region, which is located below 16°N, where the most important control is the winter monsoon circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many theoretical studies, for example, Nielsen‐Gammon (), Qian et al . () and Rotunno (), have also indicated that in low latitudes (30°N) the sea breeze circulation can occur out of phase with the diurnal heating cycle and the flow becomes antitriptic (i.e., based on local pressure gradient and friction forces). This is especially true for the SRS region, which is located below 16°N, where the most important control is the winter monsoon circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the basic dynamics of the land‐sea breeze have been explored in several recent studies (Jiang, ; Li & Carbone, ; Qian et al, ), satellite wind observations of diurnal convection‐wind coupling have not been utilized, and several important questions about the land‐sea breeze circulations in this region remain. One such question is what suppresses diurnal wind variability in the northeast side of the bay (Figures b and ); the Doppler‐shifting mechanism proposed by Li and Carbone () was shown here to be incapable of suppressing diurnal variability in the northeast side of the bay.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the diurnal gravity wave helps to initiate convection both through surface convergence, which lifts surface air, and the cool anomalies near 800 hPa, which increase the buoyancy of lifted surface air as described by Mapes et al (2003b). Although the basic dynamics of the land-sea breeze have been explored in several recent studies (Jiang, 2012;Li & Carbone, 2015;Qian et al, 2009), satellite wind observations of diurnal convection-wind coupling have not been utilized, and several important questions about the land-sea breeze circulations in this region remain. One such question is what suppresses diurnal wind variability in the northeast side of the bay (Figures 6b and 11); the Doppler-shifting mechanism proposed by Li and Carbone (2015) was shown here to be incapable of suppressing diurnal variability in the northeast side of the bay.…”
Section: Discussionmentioning
confidence: 99%
“…The following topics are not extensively discussed: pollutant dispersion models (Clappier et al 2000;Melas et al 2006), land-surface models (Cheng and Byun 2008), linear and analytical models (Rotunno 1983;Niino 1987;Dalu and Pielke 1989;Qian et al 2009;Drobinski and Dubos 2009), laboratory experiments (Simpson 1997;Cenedese et al 2000;Hara et al 2009), land breezes (Buckley and Kurzeja 1997), and convective internal boundary-layer growth Kuwagata et al 1994;Levitin and Kambezidis 1997;Liu et al 2001;Miller et al 2003).…”
Section: Figmentioning
confidence: 99%